2015
DOI: 10.1155/2015/250310
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adenylyl Cyclase Type 5 Increases Longevity and Healthful Aging through Oxidative Stress Protection

Abstract: Mice with disruption of adenylyl cyclase type 5 (AC5 knockout, KO) live a third longer than littermates. The mechanism, in part, involves the MEK/ERK pathway, which in turn is related to protection against oxidative stress. The AC5 KO model also protects against diabetes, obesity, and the cardiomyopathy induced by aging, diabetes, and cardiac stress and also demonstrates improved exercise capacity. All of these salutary features are also mediated, in part, by oxidative stress protection. For example, chronic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 142 publications
(112 reference statements)
3
29
0
Order By: Relevance
“…The liver is a central organ for the maintenance of lipid and glucose homeostasis and, due to this fact it is susceptible to oxidative stress damage [Qureshi and Abrams, ; Meng et al, ]. It is known that oxidative stress increases with aging [Vatner et al, ]. Thus, we hypothesize whether disturbances in the hepatic glucose homeostasis is related to the oxidative stress in old rats.…”
Section: Discussionmentioning
confidence: 88%
“…The liver is a central organ for the maintenance of lipid and glucose homeostasis and, due to this fact it is susceptible to oxidative stress damage [Qureshi and Abrams, ; Meng et al, ]. It is known that oxidative stress increases with aging [Vatner et al, ]. Thus, we hypothesize whether disturbances in the hepatic glucose homeostasis is related to the oxidative stress in old rats.…”
Section: Discussionmentioning
confidence: 88%
“…AC5 is a major regulator of cardiac inotropy and chronotropy, however it could also have adverse effects for the heart. In fact, in mouse models, cardiac-specific overexpression of AC5 enhanced basal cardiac performance [ 139 ], but also decreased the cardiac resistance to prolonged stress [ 140 ]. The adverse effects of AC5 overexpression are attributed to a pathway that involves the SIRT1/FoxO3a axis [ 141 ].…”
Section: Key Playersmentioning
confidence: 99%
“…The rapid progress in the understanding of the human genome has opened up new avenues for studying interactions between nutrients and the genome [ 1 ]. Up to now, it has been clearly shown that one common mechanism that mediates cellular longevity and healthful aging is protection against oxidative stress [ 2 ]. Notably, an excessively high level of reactive oxygen species (ROS) with normal levels of endogenous antioxidant enzymes is the basis for oxidative stress in the brain, which causes apoptosis and cell damage.…”
Section: Introductionmentioning
confidence: 99%